Managing Corporate Reputation in Higher Education: The Case of the North-West University - Ashleigh Pieterse; Lida Holtzhausen (Communicare, 2025)
The objective of this article is to evaluate the corporate reputation of the North-West University during a period characterised by significant challenges, such as transformation within the higher education sector and the impact of global trends such as the Covid-19 pandemic, the Fourth Industrial Revolution and the emergence of new stakeholder groups. These challenges possess the potential to affect North-West University’s corporate reputation. The article explores North-West University’s corporate reputation with an emphasis on the importance of staff members as a key stakeholder group of which to take note. The article assesses this stakeholder group’s perceptions through semi-structured interviews and an online survey characterised by RepTrak™. The findings of the article suggest that there is room for North-West University to improve its corporate reputation among staff members, as these stakeholders perceive the university’s corporate reputation as average. The findings also suggest a need to improve corporate reputation management and the need for development of a formal strategy to achieve this at North-West University. The article furthermore proposes reasons staff members at North-West University perceive the university’s corporate reputation as average and provides recommendations for improving it.